Bisphosphonates intake and its association with changes of periarticular bone area and three-dimensional shape: data from the Osteoarthritis Initiative (OAI). Issue 4 (April 2018) - Haj-Mirzaian, A.; Guermazi, A.; Roemer, F.W.; Bowes, M.A.; Conaghan, P.G.; Demehri, S.
Summary: Objective: To determine the association between bisphosphonate treatment with the change of periarticular bone area and three-dimensional (3D) shape in participants of the Osteoarthritis Initiative (OAI) study. Design: Using propensity score (PS) matching method in females, 48 bisphosphonate users and 105 non-users, who were matched for osteoarthritis (OA) and osteoporosis (OP) related factors were included. Baseline and 24-month magnetic resonance imaging (MRI)-based periarticular bone area and 3D shape measurements were used. The association between bisphosphonate intake and 24-month interval changes of the periarticular bone area and 3D shape were evaluated using paired Wilcoxon signed rank test. We used conditional logistic regression models for determining the association between bisphosphonate intake and periarticular bone change, defined using the standard deviation of difference (SDD) and reliable change index (RCI) methods. P -values have been adjusted for multiple comparisons using Benjamini & Hochberg procedure and false discovery rate (FDR)-adjusted P -values were reported. Results: The 24-month interval increases in the periarticular bone area in medial side of tibia were significantly greater in non-users than users ( FDR-adjusted P-value: 0.002 ). There was an approaching significance trend for lower medial tibial periarticular bone area expansion in bisphosphonate users in comparison with non-users (For 1SDD change, odds ratio 95% confidence interval (OR (95% CI)): 0.514 (0.271–0.975), FDR-adjusted P-value : 0.085 ) (For 1.96RCI change, OR (95% CI): 0.552 (0.309–0.986), FDR-adjusted P-value: 0.085 ). Conclusions: Bisphosphonate intake was associated with a reduction in the odds (approaching but not achieving significance) of expansion periarticular bone area, specifically in the medial tibial sub-region.